2020
DOI: 10.5194/amt-13-3205-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral characterization of primary emissions and implications in source apportionment of organic aerosol

Abstract: Abstract. Source apportionment of organic aerosol (OA) from aerosol mass spectrometer (AMS) or aerosol chemical speciation monitor (ACSM) measurements relies largely upon mass spectral profiles from different source emissions. However, the changes in mass spectra of primary emissions from AMS–ACSM with the newly developed capture vaporizer (CV) are poorly understood. Here we conducted 21 cooking, crop straw, wood, and coal burning experiments to characterize the mass spectral features of OA and water-soluble O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 68 publications
(96 reference statements)
13
32
0
Order By: Relevance
“…The four Chinese dishes had prominent peaks at m/z 41, m/z 43 and m/z 55 (generated from C3H5 + and C3H7 + , C4H7 + ) which was qualitatively consistent with mass spectra of primary COA in other studies (Xu et al, 2020). As described by He et al (2010), the most abundant ion fragments at m/z 41 and m/z 55 from primary Chinese cooking emissions are resulting from unsaturated fatty acids (He et al, 2010).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The four Chinese dishes had prominent peaks at m/z 41, m/z 43 and m/z 55 (generated from C3H5 + and C3H7 + , C4H7 + ) which was qualitatively consistent with mass spectra of primary COA in other studies (Xu et al, 2020). As described by He et al (2010), the most abundant ion fragments at m/z 41 and m/z 55 from primary Chinese cooking emissions are resulting from unsaturated fatty acids (He et al, 2010).…”
Section: Resultssupporting
confidence: 85%
“…However, based on collocated AMS measurements and factor analysis results, the SOA formed by vehicle and cooking sources cannot be effectively resolved from the total SOA due to the lack of secondary mass spectral profiles. The POA mass spectral profiles based on AMS including HOA (Collier et al, 2015), BBOA (Alfarra et al, 2007;He et al, 2010;Xu et al, 2020), and COA (He et al, 2010;Liu et al, 2017;Mohr et al, 2012;Xu et al, 2020) have been fully explored in laboratory studies, and applied as constraint factors into the ME-2 model in the ambient air. Some studies have made it possible to quantify biogenic secondary aerosol products of a single precursor, such as isoprene oxidation products (IEPOX) (Budisulistiorini et al, 2013;Hu et al, 2016b), and have been extended to the urban atmosphere to obtain an IEPOX-SOA factor via PMF analysis of OA spectra (Zhang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…x in mass spectra of SOA in winter in Beijing. The OA factors representing different sources were identified by PMF, and detailed PMF analyses from the three campaigns have been given in Xu et al (2021) and Chen et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The NO x + signals assigned to POA in winter in Beijing were much higher than those in source emission experiments. For example, f NO+ (3.5%) and f NO2+ (1.5%, fractions of NO + or NO 2 + in total mass spectrum) of biomass burning OA in winter in Beijing (Fig.S3) were higher than that from burning of different biofuels (f NO+ =0.9% and f NO2+ =0.65%) (Xu et al, 2020). Further analysis suggested that the episodes dominated by POA also resulted in higher pON loadings from the "PMF method" in winter in Beijing.…”
Section: Intercomparisonsmentioning
confidence: 97%
“…However, the separation of inorganic and organic NO x + may be limited by the bilinear model depending on the correlations between inorganic nitrate and pON. In addition, some primary organic aerosol (POA) factors from "PMF method" also contained much higher NO + or NO 2 + compared to directly measured mass spectrum of primary emissions (Xu et al, 2020) (Fig. S1), increasing the uncertainties in quantification of pON.…”
Section: Introductionmentioning
confidence: 99%